Addressing Adolescent Constipation Through Functional Snack Innovation: Narrative Review on Eucheuma Cottonii and Pleurotus Ostreatus - Rizka Indrieanie Hawarie (Yayasan Literasi Sains Indonesia, 2026)
Constipation is a common digestive disorder characterized by infrequent bowel movements, hard stools, and straining, and is particularly prevalent among adolescents due to low dietary fiber intake. Addressing this issue requires innovative approaches to improve fiber consumption through foods that are both familiar and acceptable to this age group. This narrative review explores the potential use of Eucheuma cottonii (seaweed) and Pleurotus ostreatus (white oyster mushroom) as high-fiber functional ingredients in adolescent-targeted food products. Evidence from recent studies indicates that both ingredients are rich in dietary fiber and can contribute to improved digestive health. When moderately substituted into popular food formulations such as dimsum mentai, they can enhance nutritional value while maintaining acceptable sensory characteristics. This review aims to explore the potential of these two ingredients by discussing their nutritional composition, functional roles, and sensory effects, highlighting their promise in the development of fiber-enriched snacks for constipation prevention and management in adolescents. These strategies are expected to support healthier dietary patterns and improve overall gastrointestinal well-being in this population.